Investıgatıon of Respiatory Parameters, Hand-Eye Coordinations And Body Mass Indexes of Superior Intelligence Students Between 8 and 9 Years - Akçınar, Faruk; Güllü, Mehmet; Akçınar, Serpil; Arslan, Cengiz (My University, 2020)
Abstract: The aim of this study was to investigate respiratory parameters, hand-eye coordination and body mass indexes ofgifted students aged 8-9 years. The population of the research consists of 124 students from 23,228 students in the second yearin Malatya. The research group consists of 73 students (37 girls and 36 boys). To determine students' intelligence levels as datacollection tools Wechsler Intelligence Scale for Children (Savaşır and Şahin, 1995) was applied, Mir Spirolab III brandspirometer is used for measurement of the functions, dart was performed for hand-eye coordination and weight and heightmeasurements were taken for Body Mass Index (BMI). One - way ANOVA was used for comparisons. Significance level wastested with ? = 0.05. The findings of the study showed that children with normal intelligence (n = 4) Wisc-r had a total of 105.75± 2.36; children with bright intelligence (n = 10) 114.30 ± 2.40; children with superior intelligence (n = 26) 124.30 ± 2.71; childrenwith very high intelligence (n = 22) 134.18 ± 2.48; genius group (n = 11) children were found to score 145.73 ± 3.95. There was nostatistically significant difference (p> 0.05) between FVC, FEV1, PEF, Dart mean and BMI according to intelligence groups ofchildren. As a result, there was no significant difference between respiratory parameters, hand-eye coordination and BMIaccording to intelligence levels of 8-9 years old children. Therefore, it can be said that gifted children do not have any physicaldifference compared to the children in the other intelligence group.
Keywords: Eğitim; Eğitim Araştırmaları; Spor Bilimleri